Communication of Private University Services During the Covid-19 Pandemic - Wiwitan, Tresna; Yulianita, Neni; Novita, Sophia (KnE Social Sciences, 2023)
The purpose of this study was to examine and analyze the communication of private university services during the Covid-19 pandemic. This research study was motivated by the Covid-19 pandemic that occurred in Indonesia and had a direct impact on various people’s lives, including the world of education in universities. The online learning process in the form of distance lectures is an alternative and a must in conducting lectures for students. Various problems arise when universities must carry out all activities online so that communication services at universities during the Covid- 19 pandemic are important, where students do not meet directly with lecturers and education staff. The research method used in this study was qualitative with a case study approach at universities that are partners of Universitas Islam Bandung at the Region IV Higher Education Service Institute, West Java, and Banten. The selection of research objects was carried out purposively and subjectively based on the National Accreditation Board for Higher Education, namely Universitas Sangga Buana, Sekolah Tinggi Ilmu Komunikasi Bandung, and Sekolah Tinggi Administrasi Sebelas April Sumedang. Data collection techniques are in-depth interviews with informants involved in service communication at selected private universities, observation, and literature study. The results showed that the communication of services carried out by private universities with students used e-learning, Zoom, Google meet, and Whatsapp groups. Barriers to online service communication occur when the internet network does not support it and many students go offline and do not comply with the health protocol. Keywords: service communication, relationship management, covid-19 pandemic